Speech Intonation Perception Deficits in Musical Tone Deafness (Congenital Amusia). - Patel, Aniruddh D.; Peretz, Isabelle. (Tufts University. Tisch Library., 2016)
To what extent do music and language share neural mechanisms for processing pitch patterns? Musical tone-deafness (amusia) provides important evidence on this question. Amusics have problems with musical melody perception, yet early work suggested that they had no problems with the perception of speech intonation (Ayotte, Peretz, & Hyde, 2002) However, here we show that about 30% of amusics from independent studies (British and French-Canadian) have difficulty discriminating a statement from a question on the basis of a final pitch fall or rise. This suggests that pitch direction perception deficits in amusia (known from previous psychophysical work) can extend to speech. For British amusics, the direction deficit is related to the rate of change of the final pitch glide in statements/ questions, with increased discrimination difficulty when rates are relatively slow. These findings suggest that amusia provides a useful window on the neural relations between melodic processing in language and music.